Optical gain from polyfluorene keto defects in a liquid crystal mixture. Issue 47 (14th June 2015) - Bolis, S.; Celebrano, M.; Ghirardini, L.; Finazzi, M.; Botta, C.; Beeckman, J.; Kockaert, P.; Virgili, T.
<x xml:space="preserve">Abstract</x> Confocal photoluminescence measurements and fs pump–probe spectroscopy to observe a polarized gain region from keto defects in polyfluorene isolated chains.